L'Europe en quête d'une politique de migration : les contraintes de la mondialisation et de la restructuration des marchés du travail - Overbeek, Henk (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
This paper argues that the development towards a common migration policy in the European Union reflects the emergence of a new form of regionalism resulting from the recent structural transformations in the global political economy. The European governments are caught in a web of contradictory interests and tendencies. On one side, the logic of global economic restructuring dictates continued deregulation and flexibilisation of the labour market, implying increased high levels of immigration. On the other hand, the political backlash against globalisation pushes towards a closure of the external borders. The result is the construction of a Fortress Europe, with a set of specific cooperation agreements with the regions surrounding the European Union in order to regulate the inflow of migrants.